Proximate chemical composition and mineral content of two sargassum species. - Gamarcha, Jonalyn Dasas
The salinity tolerance of three age groups (1-week-old, 2-week-old, 3-week-old fingerlings) of African catfish, Clarias gariepinus, was investigated in the laboratory using different salinity values: 1, 5, 10 and 15 ppt for three days each. They were maintained at ambient temperature and aeration was provided. Mortality of fingerlings exposed to these salinities were monitored daily. All age groups of catfish survived at 1 ppt. Treatment at 5 ppt resulted to above 50 percent survival for all groups. Fishes exposed to 10 ppt showed low percentage of survival, which is below 50 percent. Mortality was greatest at 15 ppt exposure where survival was not observed across all groups. The salinity acclimatization experiment showed that older catfish can reach higher salinities than younger ones. One-week old fingerlings were acclimatized only up to 9.5 ppt, 14 ppt in the case of two-week old while the three-week old fingerlings tolerated up to 15 ppt. This study indicates that Clarias gariepinus can tolerate salinities below or equal to 5 ppt. This anrrow range of salinity tolerance is attributed, to the fish' stenohaline nature. It also shows that older Clarias gariepinus fingerlings is more suited for salinity acclimatization.